14.9k views
2 votes
Help I don’t get this one question

Help I don’t get this one question-example-1

2 Answers

4 votes
the answer would be A. -18x^7

hope this helps:)
User Kishan Bharda
by
5.5k points
3 votes

Answer:


-6x^2\left(3x^5\right)=-18x^7

Hence, option (A) is true.

Explanation:

Given the expression


-6x^2\left(3x^5\right)


\mathrm{Apply\:exponent\:rule}:\quad \:a^b\cdot \:a^c=a^(b+c)

i.e.
x^2x^5=\:x^(2+5) \\

so the expression becomes


-6x^2\left(3x^5\right)=-6\cdot \:\:3x^(2+5)


\mathrm{Add\:the\:numbers:}\:2+5=7


=-6\cdot \:3x^7


\mathrm{Multiply\:the\:numbers:}\:6\cdot \:3=18


=-18x^7

Therefore,


-6x^2\left(3x^5\right)=-18x^7

Hence, option (A) is true.

User Abimbola
by
5.4k points